2018
DOI: 10.3390/ijms19061689
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome-Gut-Brain Axis and Toll-Like Receptors in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a progressively debilitating neurodegenerative disease characterized by α-synucleinopathy, which involves all districts of the brain-gut axis, including the central, autonomic and enteric nervous systems. The highly bidirectional communication between the brain and the gut is markedly influenced by the microbiome through integrated immunological, neuroendocrine and neurological processes. The gut microbiota and its relevant metabolites interact with the host via a series of biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
232
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(243 citation statements)
references
References 129 publications
(147 reference statements)
2
232
0
9
Order By: Relevance
“…The possible pieces of evidence supporting the efficacy of probiotics in PD could be related to the alternation of PD-associated microbiota composition, improvement of GI function, reduction of harmful gut bacteria, gut leakiness, bacterial translocation, proinflammatory cytokines, oxidative stress, potentially pathogenic bacterial overgrowth, and the associated neural inflammation in the ENS [24][25][26][27]30,55]. In addition, to enhance the effects of anti-inflammation and anti-oxidative stress in the GI system, combining the probiotics and other drug treatments (e.g., anandamide or calcitonin gene-related peptide) may have better effects to inhibit the inflammatory process and preserve the integrity of gastric mucosa, by improving the endogenous release of nitric oxide (NO) and increasing the blood flow [13,21,[56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possible pieces of evidence supporting the efficacy of probiotics in PD could be related to the alternation of PD-associated microbiota composition, improvement of GI function, reduction of harmful gut bacteria, gut leakiness, bacterial translocation, proinflammatory cytokines, oxidative stress, potentially pathogenic bacterial overgrowth, and the associated neural inflammation in the ENS [24][25][26][27]30,55]. In addition, to enhance the effects of anti-inflammation and anti-oxidative stress in the GI system, combining the probiotics and other drug treatments (e.g., anandamide or calcitonin gene-related peptide) may have better effects to inhibit the inflammatory process and preserve the integrity of gastric mucosa, by improving the endogenous release of nitric oxide (NO) and increasing the blood flow [13,21,[56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism is the anti-inflammation effects of probiotics. It has been found that PD patients have greater intestinal permeability (gut leakiness), which might upregulate the local/systemic inflammatory response and oxidative stress induced by lipopolysaccharides (LPSs, also termed endotoxin), leading to α-synucleinopathy in the enteric nervous system [13]. Furthermore, the higher levels of gut-derived LPSs could promote the neuroinflammation and damage in substantial nigra via the disruption of blood-brain barrier (BBB) integrity [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of ␣S in the setting of an infectious insult would initially attract protective immune cells, followed by the engagement of the adaptive immune system. As yet we do not know the mechanisms that are involved in the induction of neuronal ␣S by infection, such as the role of TLRs (which are present on neurons) [29,30], or the release of pro-inflammatory mediators, such as IL-17 and IL-22 (which potently stimulate induction of epithelial AMPs) [31].…”
Section: Neuronal ␣S Chemoattracts Immune Cells To Confine Infectionmentioning
confidence: 99%
“…The efficacy of some probiotics against diarrhoea has been reported [33], as well as providing intestinal microbial balance [34], reduces the risk of colon and breast cancer [35], reduces blood pressure [17,[22][23][24]36], reduces lipid profiles [37], reduces allergies and food intolerances [38], inhibits the growth of pathogenic bacteria and is immunomodulatory [12,[39][40][41][42] (Figure 1). More recently, dysbiosis has been implicated to be involved in the pathogenesis of a number of disorders such as, Sjogren's syndrome [43], Parkinson's disease [44] and multiple sclerosis [45]. The use of probiotics and prebiotics could be used as therapeutic approaches against diseases.…”
Section: Health Benefits Of Fermented Milk Productsmentioning
confidence: 99%